State and Fault Observer Design for Switched Systems via an Adaptive Fuzzy Approach - Chen, Liheng; Fu, Shasha; Zhao, Yuxin; Liu, Ming; Qiu, Jianbin (IEEE transactions on fuzzy systems, 2020)
This article investigates the state and fault estimation problem for switched systems with external disturbances, unknown nonlinear dynamics, and actuator and sensor faults. In this article, a new adaptive fuzzy-based observer is designed, where the prior knowledge of the nonlinearities, disturbances, and faults is not required. In contrast to the sliding mode observer (SMO), the proposed observer can guarantee the convergence of the error trajectory through the online adaptive mechanism, avoiding the sliding surface switching problem in SMO design. The accurate state asymptotic estimations can also be provided by the developed design approach subject to the simultaneous additive and multiplicative faults. Finally, a simulation example is presented to show the effectiveness of the proposed method.